1990
DOI: 10.1002/jbt.2570050105
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in polyamines and related enzymes following chlordecone‐potentiated bromotrichloromethane hepatotoxicity

Abstract: The mechanism by which chlordecone (CD) amplifies the hepatotoxicity of halomethanes such as CCl4, CHCl3, and BrCCl3 has been a subject of intense study. Recent work has shown that suppression of hepatocellular regeneration leads to accelerated progression of liver injury leading to complete hepatic failure due to an unusual interaction between individually nontoxic low-dose combination of CD and CCl4. Since polyamines are involved in cell division, their levels reflect the extent to which there is suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, literature reports provide insights into possible mechanisms. Studies have indicated that polyamine synthesis was decreased and catabolism was increased in the livers of rats that were exposed to hepatotoxic BrCCl 3 , a close analog of CCl 4 , leading to hindered stimulation of liver regeneration (Rao, Young, and Mehendale 1990). The ability of polyamines to inhibit lipid peroxidation in phospholipid liposome suspensions and rat liver homogenates, which is a cause of cell membrane damage, has been demonstrated (Pavlovic et al 1992).…”
Section: Figurementioning
confidence: 99%
“…However, literature reports provide insights into possible mechanisms. Studies have indicated that polyamine synthesis was decreased and catabolism was increased in the livers of rats that were exposed to hepatotoxic BrCCl 3 , a close analog of CCl 4 , leading to hindered stimulation of liver regeneration (Rao, Young, and Mehendale 1990). The ability of polyamines to inhibit lipid peroxidation in phospholipid liposome suspensions and rat liver homogenates, which is a cause of cell membrane damage, has been demonstrated (Pavlovic et al 1992).…”
Section: Figurementioning
confidence: 99%